New Insights into Wideband Synthetic Aperture Radar Interferometry - Mustieles Perez, Victor; Kim, Sumin; Krieger, Gerhard; Villano, Michelangelo (IEEE Geoscience and Remote Sensing Letters, 2024)
Synthetic aperture radar interferometry (InSAR) is a technique that exploits the phase difference between two synthetic aperture radar (SAR) images to generate digital elevation models (DEMs) of the imaged terrain. InSAR has a well-established theoretical background, but approximations for narrowband signals are often made. To unwrap the interferometric phase, dual-baseline techniques are also commonly employed. Modern InSAR systems will use wider bandwidths to improve the accuracy and resolution of the DEMs. This letter generalizes the expressions of the baseline decorrelation and the critical baseline for InSAR systems with wide bandwidths and large baselines, where the spectral shrinkage is not negligible. It is also shown that radargrammetry offers high potential to unwrap the interferometric phase already on a pixel-by-pixel basis. The proposed approach can also exploit acquisitions with multiple baselines or frequency bands. The results show that a single wideband interferometric acquisition may suffice to perform phase unwrapping for high interferometric coherences. The concepts discussed in this paper will help to design and enhance the performance of future wideband and multi-band InSAR missions to deliver a new generation of DEMs with unprecedented resolution and accuracy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: drones; interferometric coherence; multi-band; radargrammetry; SAR interferometry; spectral shift; Synthetic aperture radar (SAR); unmanned aerial vehicle (UAV); wide bandwidth